Fire protection engineering in building design - Lataille, Jane I. (Plant engineering)
A clear and concise reference guide on integrating fire protection design, Fire Protection Engineering in Building Design encompasses not only the basic information on the functions, design, and applications of fire protection systems; but also reveals how this information can and should be integrated with every other major engineering discipline. Protecting people, buildings and the environment from the impact of fire requires a comprehensive, systematic approach that includes the analysis of fire hazards as well as the design, installation and maintenance of fire detection, suppression and c.